2020
DOI: 10.1016/s1473-3099(20)30016-5
|View full text |Cite
|
Sign up to set email alerts
|

Safety, reactogenicity, and immunogenicity of a chimpanzee adenovirus vectored Ebola vaccine in adults in Africa: a randomised, observer-blind, placebo-controlled, phase 2 trial

Abstract: Background: The 2014 Zaire Ebola virus disease epidemic accelerated vaccine development for the virus. We aimed to assess the safety, reactogenicity, and immunogenicity of one dose of monovalent, recombinant, chimpanzee adenovirus type-3 vectored Zaire Ebola glycoprotein vaccine (ChAd3-EBO-Z) in adults. Methods This phase 2, randomised, observer-blind, controlled trial was done in study centres in Cameroon, Mali, Nigeria, and Senegal. Healthy adults (≥18 years) were randomly assigned with a web-based system (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Owing to their lower seroprevalence and thus decreased vector neutralization in humans as compared to human Ad5, chimpanzee Ad (ChAd) vectors represent an attractive vaccine platform (3)(4)(5). ChAdvectored candidate vaccines against infectious diseases such as malaria, Ebola, and RSV have shown favorable immunogenicity and tolerability in humans (6)(7)(8)(9)(10)(11). These vaccines drive robust intracellular antigen expression, thus promoting a CD8 + T-cellbiased response, but were also shown to induce antigen-specific CD4 + T-cell responses and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their lower seroprevalence and thus decreased vector neutralization in humans as compared to human Ad5, chimpanzee Ad (ChAd) vectors represent an attractive vaccine platform (3)(4)(5). ChAdvectored candidate vaccines against infectious diseases such as malaria, Ebola, and RSV have shown favorable immunogenicity and tolerability in humans (6)(7)(8)(9)(10)(11). These vaccines drive robust intracellular antigen expression, thus promoting a CD8 + T-cellbiased response, but were also shown to induce antigen-specific CD4 + T-cell responses and antibodies.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the same adenovirus vector expressing the full-length S protein of MERS-CoV was also evaluated in a phase I human trial and demonstrated good safety and tolerability 4 . ChAd3 vectors expressing Ebola Zaire glycoprotein (ChAd3-EBO-Z) elicited strong immune responses in clinical trial participants 34,35 . These results highlight the favorable safety, tolerability, and immunogenicity profiles of chimpanzee adenovirus vector-based vaccines in humans, which hold great promise for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…This is in great contrast to the immunity induced by other candidate vaccines, for which immunogenicity is short-lived and multiple rounds of immunization are required to induce detectable levels of neutralizing antibodies or to confer protection against viral challenge 1,30 . Furthermore, recombinant vaccines based on AdC68 and other rare serotype chimpanzee adenoviral vectors, such as ChAd63 and ChAd3, have recently been engineered to express various antigens, with some demonstrating impressive safety and immunogenicity profiles in clinical studies [31][32][33][34][35] . These unique features and our prior experience in handling the chimpanzee adenovirus vectors provided a critical foundation and rationale for the development of a SARS-CoV-2 vaccine based on ChAdTS.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Ad-based vaccine applications, two phase II clinical trials have been conducted for Ebola virus vaccines [26,27]. The simian ChAdOx1 vector expressing the Ebola virus glycoprotein (ChAd3-EBO-Z) was administered to 1509 adults, and although injection site pain and serious non-vaccine related events were recorded, no clinically meaningful thrombocytopenia was registered [26]. In the other phase II trial, the ChAd3-EBO-Z vaccine was administered to 300 healthy children, six years old or younger [27].…”
Section: Adenovirus-induced Thrombocytopeniamentioning
confidence: 99%